Tantangan dan Solusi dalam Manajemen Kurikulum di Era Digital - Apri Chesa Fournanda; Hanifiyah Zahra; Marsya Dwi Anjelina; Merika Setiawati; Hendri Budi Utama (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Curriculum management is a science that studies the planning, implementation and evaluation of a school curriculum including in the digital era. The purpose of this article is to discuss the various challenges and solutions in curriculum management in the digital era. In addition, literature studies and qualitative approaches are used as research methods in writing this article. And then, the results of the study show that there are various challenges in curriculum management in the digital era. More precisely, there are eight challenges faced. These challenges are challenges that come from infrastructure, access, human resources, technological changes to global shifts. Therefore, various solutions are also provided to face the various challenges. The solutions provided do not only involve one party but involve various stakeholders, including parents, educators, technology experts, and of course support from the government and other educational institutions.